The three occupied UAE islands the Tunbs and Abu Musa - Mattair, Thomas R. (Emirates Center for Strategic Studies and Research, 2014)
The issue of the three occupied UAE islands in the Persian Gulf - the Greater and Lesser Tunbs and Abu Musa - deserves particular attention because it threatens to undermine regional security and has potential global implications. This study assesses the legal and sovereign rights of the United Arab Emirates over the three islands